2018
DOI: 10.1021/acs.jmedchem.8b00807
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Glucuronide Metabolites of 6-Chloro-5-[4-(1-hydroxycyclobutyl)phenyl]-1H-indole-3-carboxylic Acid (PF-06409577) and Related Indole-3-carboxylic Acid Derivatives are Direct Activators of Adenosine Monophosphate-Activated Protein Kinase (AMPK)

Abstract: Studies on indole-3-carboxylic acid derivatives as direct activators of human adenosine monophosphate-activated protein kinase (AMPK) α1β1γ1 isoform have culminated in the identification of PF-06409577 (1), PF-06885249 (2), and PF-06679142 (3) as potential clinical candidates. Compounds 1-3 are primarily cleared in animals and humans via glucuronidation. Herein, we describe the biosynthetic preparation, purification, and structural characterization of the glucuronide conjugates of 1-3. Spectral characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 65 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…Interestingly, these amino acid residues are considered the binding domains of AMPK agonists. 44,45 When 10-G binds to AMPKα and β, it increases the interaction etween…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these amino acid residues are considered the binding domains of AMPK agonists. 44,45 When 10-G binds to AMPKα and β, it increases the interaction etween…”
Section: Discussionmentioning
confidence: 99%
“…PF-06409577 is commercially available from Sigma Aldrich (St. Louis, MO). The biosynthetic methodology (scale-up of UDPGA-supplemented HLM incubations of PF-06409577) for preparation of the acyl glucuronide M1 has been previously described (Ryder et al, 2018). Examination of the degradation kinetics of the biochemically isolated M1 in deuteriated phosphate buffer (pH ;7.4) at 37°C using a NMR method developed to monitor the disappearance of the anomeric proton (d;5.7-5.8 ppm) in b-O-1-acyl glucuronides revealed that M1 was inert toward hydrolysis or acyl migration (half-life .…”
Section: Methodsmentioning
confidence: 99%
“…Examination of the degradation kinetics of the biochemically isolated M1 in deuteriated phosphate buffer (pH ;7.4) at 37°C using a NMR method developed to monitor the disappearance of the anomeric proton (d;5.7-5.8 ppm) in b-O-1-acyl glucuronides revealed that M1 was inert toward hydrolysis or acyl migration (half-life . 21 hours) (Ryder et al, 2018). As a general precaution, solid material corresponding to parent (PF-06409577) and acyl glucuronide (M1) was stored in sealed vials under argon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations